Characteristics of the clinical education role as perceived by registered nurses working in the practice setting : a thesis presented in partial fulfillment of the requirements for the degree of Master of Philosophy in Nursing at Massey University - Orchard, Stephenie Helen (Massey University, 1999)
Although clinical education has long been acknowledged as the heart of nursing education, the role of the nurse lecturer in relation to the clinical learning experience of nursing students, is an area of long standing confusion and dispute. The many advances in technology, nursing science, and the professional role, have not been accompanied by substantive change in the approach to clinical education. Research to date has focused on the lecturers' and students' perceptions of the clinical education role. This study describes the characteristics of the clinical education role as perceived by ten registered nurses working a practice setting. The participants in the study were employed by a Crown Health Enterprise which has for many years, served as a clinical practice agency for a department of nursing within an educational institute. All the participants were employed as registered nurses within the general medical and surgical wards. A qualitative, descriptive and exploratory study was undertaken. Face to face, semi-structured interviews were used to obtain data. This was then analysed using thematic content analysis. Findings from the data revealed five characteristics of the clinical education role as perceived by Registered Nurses working in the practice setting. The clinical education role in its present form changes registered nurses relationship with their patients and changes their pattern of work. It requires good communication with nurse lecturers, preparation for the role, and needs to provide nursing students with the opportunity to learn.
Keywords: Clinical medicine; Study and teaching; Nursing; New Zealand